On Dialogue and the Other An Interview with Edmond Jabès - Richard Stamelman (Studies in 20th & 21st Century Literature, 1987)
The interview look place in Paris on May 30, 1985, at the home of Edmond Jabès.
Keywords: interview; Edmond Jabès; Jew; Jewish; religion; writing; self-reflection